Dampak dari penyajian kembali laporan kuangan terhadap pergantian auditor perusahaan publik di Indonesia - Cindy, Cindy; Supriyanto, Supriyanto (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
Auditor switching is the termination of a relationship and the replacement of a public audit service relationship with a Public Accountant or Public Accounting Firm carried out by the company as a service user. This study aims to analyze the factors that led to the auditors change. These factors include restatement of financial statements, corporate governance, KAP size and CEO turnover. The sample of this research is all companies listed on the IDX for the 2016-2020 period. The research method that the researcher uses to examine this research is a quantitative research method to test hypotheses where the sample of data sources is carried out by purposive sampling. Testing of the research hypotheses was carried out using logistic regression analysis. The test results show that the restatement of financial statements, corporate governance, the size of the public accounting firm and CEO turnover have no significant effect on auditor turnover.